2021
DOI: 10.1177/03000605211022967
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between matrix metalloproteinase-2 polymorphisms and first and recurrent atherosclerotic ischemic stroke events: a case–control study

Abstract: Objective To determine the associations between matrix metalloproteinase-2 (MMP-2, encoded by the MMP2 gene) 1306C/T and 735C/T polymorphisms and first and recurrent ischemic stroke in a Chinese population. Methods Patients with first and recurrent ischemic stroke were included. Serum MMP-2 was measured, and MMP2 1306C/T and 735C/T polymorphisms were detected. The associations between MMP2 1306C/T and 735C/T polymorphisms and first and recurrent ischemic stroke were analyzed. Results Serum MMP-2 in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The regulatory role of MMP2 may be related to the regulation of its genetic variation. Li et al ( 13 ) illustrated that compared with the normal control group, the frequency of CC genotype and C allele of MMP2 735C/T in the first and recurrent IS in the Chinese population were significantly increased, and the frequency of IS recurrence was more significant. Previous studies demonstrated that rs243849 in MMP2 evidently reduced the risk of IS in Hainan population, while rs1053605 in MMP2 was not found to be associated with IS susceptibility ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The regulatory role of MMP2 may be related to the regulation of its genetic variation. Li et al ( 13 ) illustrated that compared with the normal control group, the frequency of CC genotype and C allele of MMP2 735C/T in the first and recurrent IS in the Chinese population were significantly increased, and the frequency of IS recurrence was more significant. Previous studies demonstrated that rs243849 in MMP2 evidently reduced the risk of IS in Hainan population, while rs1053605 in MMP2 was not found to be associated with IS susceptibility ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only 3 SNPs in MMP2 were explored, and we will continue to explore the association of other SNPs in MMP2 , MMPs and gene interactions with IS susceptibility in the future ( 16 ). Additionally, the current study was limited to a single ethnic group, other ethnic groups should be validated in the future ( 13 , 17 ). Finally, in order to further determine the potential impact of MMP2 genetic variation on the risk of IS, cell and animal models will be required to verify its regulatory mechanism in different stages of IS ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that gene polymorphisms play an important role in atherosclerotic IS (Malik et al., 2018 ). In recent years, people have become increasingly interested in the study of matrix metalloproteinases (MMPs) and their relationship with the pathogenesis of atherosclerotic cerebrovascular disease (Chehaibi et al., 2014 ; Li et al., 2021 ; Wang & Khalil, 2018 ).…”
Section: Introductionmentioning
confidence: 99%